Philosophers in the public sphere of the cities - the birth of the national philosophies from the spirit of the editorial offices and saloons in the 19th century - Mester, Béla (Creativity Studies, 2011)
The aim of our paper is to offer an analysis of the phenomenon of the national philosophy of the 19th century. We will analyse this concept as a consequence of the emergence of the public sphere of the city in the function of the cultural capital of a national culture and the centre of the press. Our instance is the development of the philosophical public sphere of the double cities on the opposite banks of the Danube, Buda and Pest (today Budapest). This public sphere was organised in native language by the newly established organisations of the literature, humanities and sciences, such as different societies of writers, with a distinguished role of the Hungarian Academy of Sciences (HAS, since 1825). By our hypothesis, it is not an accident phenomenon that the topic of the national philosophy has emerged within the framework of this new public sphere. Expressed more clearly, the concept of the national philosophy depends on a special grade of the development of the public sphere of the centre of the national press – at least in the Hungarian case.Filosofai viešojoje miestų erdvėje: nacionalinių filosofijų atsiradimas redaktorių biurų ir salonų atmosferoje XIX amžiujeSantrauka. Straipsnio tikslas – pateikti XIX a. nacionalinės filosofijos fenomeno analizę. Šis konceptas čia analizuojamas kaip viešosios miesto sferos iškilimo rezultatas, neatsiejamas nuo nacionalinės kultūros ir spaudos centro kultūrinio kapitalo. Tiriama dvejopų miestų filosofinės viešosios sferos raida kaip priešprieša Danubės, Budos ir Pešto (šiandien Budapešto) bankams. Ši viešoji sfera buvo organizuojama gimtą ja kalba naujai įsteigtų literatūros, humanitarinų ir kitų mokslų organizacijų, tokių kaip skirtingos rašytojų bendruomenės, ypatingą vaidmenį atliekant Vengrijos mokslų akademijai (nuo 1825 m.). Pagal čia pateikiamą hipotezę neatsitiktinai nacionalinės filosofijos tema iškilo naujoje viešojoje sferoje. Tiksliau tariant, nacionalinės filosofijos konceptas priklauso nuo atitinkamai besiplėtojančios nacionalinės spaudos centro viešosios sferos – bent jau Vengrijos atveju.Reikšminiai žodžiai: Buda ir Peštas, miestas kaip intelektinė erdvė, ankstyvoji XIX a. Vengrija, nacionalinė kultūra, nacionalinė filosofija, spauda, viešoji sfera.